2017
DOI: 10.1016/j.ifset.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the structural and physicochemical properties of two food derived antihypertensive tri-peptides, Isoleucine-Proline-Proline and Leucine-Lysine-Proline encapsulated into a chitosan based nanoparticle system

Abstract: Some rights reserved. For more information, please see the item record link above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…Additionally, this result is in agreement with previous studies, reporting a diffusion and zero order kinetic profile for IPP and LKP loaded CsNPs, coated with zein (Danish et al, 2017a) and that of other researchers, who observed that zein proved to be a good coating for NPs, whereby, the stronger the interaction of the load material (in this instance phenolic monoterpenes) with that of the wall material (zein) was evidenced by its controlled release over time (da Rosa et al, 2015).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Additionally, this result is in agreement with previous studies, reporting a diffusion and zero order kinetic profile for IPP and LKP loaded CsNPs, coated with zein (Danish et al, 2017a) and that of other researchers, who observed that zein proved to be a good coating for NPs, whereby, the stronger the interaction of the load material (in this instance phenolic monoterpenes) with that of the wall material (zein) was evidenced by its controlled release over time (da Rosa et al, 2015).…”
supporting
confidence: 93%
“…The NP formulations were then concentrated under vacuum (175 mbar) at 40 °C until EtOH was completely removed. To ensure stability of the optimised formulation after lyophilisation, 10 mL of the cryoprotectant trehalose 5 % w/v in H 2 O was added to each formulation and lyophilised for 36 hr (Danish et al, 2017a). 228 229…”
Section: Coating Nps With Zein To Increase Ee%mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, systemic availability showed XPP (X refers to Val, Ile, and Leu) in a meal in the presence of other macronutrients had a prolonged portal bioavailability of 0.2% to 0.3% (Ten Have et al, 2015); in addition, the permeation of IPP could be enhanced by the medium chain fatty acids (Gleeson, Heade, Ryan, & Brayden, 2015). Danish, Vozza, Byrne, Frias, and Ryan (2017) formulated IPP and leu-Lys-Pro (LKP) into a chitosan nanoparticle to improve permeation. These results revealed the low permeation and low bioavailability of tripeptides can be improved by concomitant intake with meal or formulation with other carriers.…”
Section: The Bioavailability Of Ipp and Vppmentioning
confidence: 99%